STUDENTS OPINION ON EFFECTIVENESS OF CBL IN ARMY MEDICAL COLLEGE, RAWALPINDI, PAKISTAN: Effectiveness of CBL - Aleem, Shoaib Bin; Imam, Kamil Asghar; Hammad, Muhammad (Pakistan Armed Forces Medical Journal, 2014)
Objectives: To assess students’ opinion regarding group working, quality of learning and assessment in newly introduced case based learning at Army Medical College, Pakistan. Study Design: Descriptive study Place and Duration of Study: Army Medical College, 03 months. Subjects and Methods: In this study, students from the second year MBBS class at Army Medical College were given a questionnaire on completion of their second year of medical school (2012) regarding their opinion about CBL. The questionnaire used in this study consisted of 18 statements with Likert-type responses ranging from Strongly Agree (1) to Strongly Disagree (5). Statements were grouped using 3 categories: Group working, Quality of Learning and Assessment. Results: Process of learning through group work and problem solving as a learning tool was appreciated by >80%of students.Also, >84%acknowledged that CBL has prompted them to come well prepared in the session and has helped them in improving their understanding of key concepts.>83% students opine that their efforts in CBL discussions are being evaluated fairly. Conclusion: Feedback from the students clearly asserts superiority of CBL in imparting knowledge, cultivating the habit of self-learning and inculcating skills of group discussions which is in consistence with the published literature. At the same time, weak points highlighted by the students need rectification.